Primary School Teachers' Attitudes towards Inclusive Education in Slovenia: A Qualitative Exploration (Journal of Universal Excellence, 2026)
Research Question (RQ): What are the attitudes of Slovenian primary school teachers towards the inclusion of children with special needs into regular school programs?Purpose: The purpose of the study was to encourage teachers to share and reflect on their personal experiences with inclusive education in Slovenia. This could help in the development of more successful models of practice.Method: This was a qualitative study. Focus interviews and individual, semi-structured interviews were conducted. Data was analyzed using qualitative content analysis.Results: Five categories emerged from the data. This article focuses on three of the categories and explores the robust division of teachers into two groups depending on their overall attitudes towards the inclusion and children with special needs.Organization: The findings of this study suggest that Slovenian education system is not fully transitioned into the inclusive model. Teacher training and practical support are often insufficient and inter-professional cooperation is not always satisfactorily established.Society: Inclusion of children with special needs reflects the quality of the whole school system and has implications for the functioning of the society.Originality: This study deepened the understanding of the phenomenon of inclusion and linked the findings with international studies on inclusion.Limitations / further research: Future research should explore the development and implementation of relevant teaching programs and courses as well as the development of better support networks within an inclusive model of education that should champion collaboration and cooperation.
Keywords: children with special needs; inclusion; education; teacher’s attitudes; qualitative study; models of practice